Treatment preferences among adults with normal cognition and cognitive impairment. Issue 12 (12th September 2022) - Owsley, Kelsey M.; Langa, Kenneth M.; Macis, Mario; Nicholas, Lauren Hersch
Abstract: Background: Although patient participation in treatment decisions is important for preference‐concordant care delivery, it is largely unknown how cognitive impairment influences treatment preferences. We investigated whether treatment preferences for the care of serious illness differ between adults with and without cognitive impairment in hypothetical clinical scenarios. Methods: Data from the 2018 Health and Retirement Study were used. The sample included 1291 self‐respondents (201 respondents with cognitive impairment, and 1090 with normal cognition). We examined treatment preferences for life‐extending, limited, and comfort care options in two hypothetical clinical scenarios where the respondent imagines a patient with (1) good physical health with severe cognitive impairment consistent with dementia; and (2) with physical impairment due to a heart attack, but normal cognition. Respondents specified whether they were unsure, or if they would want or not want each treatment option. Linear probability models were used to compare treatment preferences by cognitive status. Results: Respondents with cognitive impairment were more likely to report that they were unsure about treatment options across both clinical scenarios compared to those with normal cognition. For the limited treatment option, cognitive impairment was associated with a lower rate of expressing a treatment preference by 7.3 ( p  = 0.070) and 8.5 ( p  = 0.035) percentage points for dementia and heart attack scenarios, respectively. Among those who articulated preferences, cognitive impairment was associated with a higher rate of preference for life‐extending treatment in both dementia (30.1% vs. 20.0%, p  = 0.044) and heart attack scenarios (30.0% vs. 20.2%, p  = 0.033). Conclusions: Compared to those with normal cognition, cognitive impairment was associated with greater uncertainty about treatment preferences and higher rates of aggressive care preferences among those who specified preferences. Further research should assess whether preferences for aggressive care become more common as cognition declines in order to improve preference‐concordant care delivery for patients with cognitive impairment.